Innovative surface bio-functionalization by fungal hydrophobins and their engineered variants - Stanzione, Ilaria; Pitocchi, Rossana; Pennacchio, Anna; Cicatiello, Paola; Piscitelli, Alessandra; Giardina, Paola (Frontiers in Molecular Biosciences, 2022)
Research for innovative surface functionalization strategies to develop materials with high added value is particularly challenging, since this process is a crucial step in a wide range of fields (i.e., biomedical, biosensing, food packaging). Up to now, the main applied derivatization methods require hazardous and poorly biocompatible reagents, harsh conditions of temperature and pressure and are time consuming and costs effective. The discovery of biomolecules able to adhere by non-covalent bonds on several surfaces paves the way for their employment as a replacement of chemical processes. A simple, fast, and environmentally friendly method of achieving modification of chemically inert surfaces is offered by hydrophobins, small amphiphilic proteins produced by filamentous fungi. Thanks to their structural characteristics, they form stable protein layers at interfaces, serving as anchoring points that can strongly bind molecules of interest. In addition, genetic engineering techniques allows production of hydrophobins fused to a wide spectrum of relevant proteins, providing further benefits in term of time and ease of the process. In fact, it is possible to bio-functionalize materials by simply dip-casting, or by direct deposition, rendering them exploitable, for example, in the development of biomedical and biosensing platforms.